Resveratrol suppresses neuroinflammation to alleviate mechanical allodynia by inhibiting Janus kinase 2/signal transducer and activator of transcription 3 signaling pathway in a rat model of spinal cord injury - Han, Jie; Hua, Zhen; Yang, Wen-jie; Wang, Shu; Yan, Fang; Wang, Jun-nan; Sun, Tao (Frontiers in Molecular Neuroscience, 2023)
Background: Neuropathic pain (NP) is one of intractable complications of spinal cord injury (SCI) and lacks effective treatment. Resveratrol (Res) has been shown to possess potent anti-inflammatory and anti-nociceptive effects. In this study, we investigated the analgesic effect of Res and its underlying mechanism in a rat model of SCI. Methods: The rat thoracic (T10) spinal cord contusion injury model was established, and mechanical thresholds were evaluated during an observation period of 21 days. Intrathecal administration with Res (300 µg/10 µl) was performed once a day for 7 days after the operation. On postoperative day 7, the expressions of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) were determined by enzyme-linked immunosorbent assay (ELISA) and Real-time quantitative PCR (RT-qPCR), the expression of Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway was determined by western blot and RT-qPCR, and the co-labeled phospho-STAT3 (p-STAT3) with neuronal nuclear antigen (NeuN), glial fibrillary acidic protein (GFAP), and ionized calcium-binding adapter molecule 1 (Iba-1) were explored by double immunofluorescence staining in the lumbar spinal dorsal horns. The temporal changes of p-STAT3 were investigated by western blot on the 1st, 3rd, 7th, 14th, and 21st days after the operation. Results: Intrathecal administration with Res for 7 successive days alleviated mechanical allodynia of rats during the observation period. Meanwhile, treatment with Res suppressed the production of pro-inflammatory factors TNF-α, IL-1β and IL-6, and inhibited the expressions of phospho-JAK2 and p-STAT3 in the lumbar spinal dorsal horns on postoperative day 7. Additionally, the protein expression of p-STAT3 was significantly increased on the 1st day following the operation and remained elevated during the next 21 days, immunofluorescence suggested that the up-regulated p-STAT3 was co-located with glial cells and neurons. Conclusion: Our current results indicated that intrathecal administration with Res effectively alleviated mechanical allodynia after SCI in rats, and its analgesic mechanism might be to suppress neuroinflammation by partly inhibiting JAK2/STAT3 signaling pathway.